CARBAMAZEPINE INDUCED HYPERSENSITIVITY SYNDROME- A CASE REPORT - Mounika, K; V Sangram (International Journal of Ayurveda and Pharma Research, 2015)
Anti-convulsant drugs elicited hypersensitivity syndrome could be a rare side effect of the primary line anticonvulsive medication like carbamazepine and alternative aromatic agents. We here mention a rare case of gastrointestinal and skin findings associated with carbamazepine administration that is incredibly uncommon and desires to be reportable. We report a study done on a 22-year woman with carbamazepine associated hypersensitivity syndrome, who developed diarrhea, fever and skin lesions. On withdrawal of carbamazepine and administration of methylprednisolone in the patient, all initial skin related symptoms, GIT symptoms were relieved and white blood corpuscle count normalized. Anticonvulsive drug hypersensitivity syndromes can present with a wide spectrum of unspecific symptoms, which the prescribing clinician should be aware of.